Rail Grease Formulation Effect on Its Tribological Performance Under Pure Sliding Conditions. Issue 1 (2nd January 2023) - Ferrer, B.P.; Biazon, L.; Zuin, A.; Tayer, P.; Toro, A.; Cousseau, T.
Abstract: The rail grease formulation effect in friction, wear, and grease loss due to centrifugal force was evaluated through pin on disc and free flow tests. Six greases were fully formulated so that the effects of the thickener and the base oil viscosity on grease performance could be isolated, since these greases have the same consistency and additive package but different base oil viscosities (50, 200, and 500 cSt) and thickener types (lithium and calcium). The results showed that: (a) lithium greases present lower friction but higher wear than calcium grease; (b) higher kinematic viscosity produces lower wear but higher friction regardless of the thickener type; (c) the critical speed at which grease is expelled from the disc increases with viscosity for lithium-thickened greases and does not depend on viscosity for calcium greases; and (d) lithium greases with high base oil viscosity suit best the wheel–rail interface lubrication, which was verified with the aid of a grease performance index proposed in the present work.